Evaluasi Pilihan Pemerintah untuk Mengatasi Pengangguran Sarjana dan Meningkatnya Kemiskinan di Aceh Barat: Evaluation of the Government's Options for Addressing Undergraduate Unemployment and Rising Poverty in Aceh Barat - Tahani Al Tuffahati; Ikhwan Rahmatika Latif; Syarah Arifa; Muntaha Mardhatillah (JOURNAL OF GOVERNMENT SCIENCE, 2023)
The purpose of this research is to examine the West Aceh District's strategy for overcoming undergraduate unemployment and reaching the poverty level. This study uses a qualitative descriptive method by examining various government policy strategies that have been proposed to do so. The results of the study found that the government had issued several policies aimed at reducing poverty due to high unemployment, such as issuing permits to open business locations in various fields in West Aceh, issuing permits for establishing large companies after fulfilling special procedures and requirements, implementing pre-employment programs, and implementing programs for productive workforce training at the West Aceh job training center.